Partisipasi Masyarakat dalam Penyusunan Peraturan Kampung di Merangkai, Dayun, Kabupaten Siak - Mexsasai Indra; Dessy Artina; Belli Nasution; Adlin Adlin; Asiah Wasillah; Winda Ersa Putri; Sukamarriko Andrikasmi; Fahrur Rozi (Unri Conference Series: Community Engagement, 2025)
This community service activity was carried out in Merangkai Village, Dayun District, Siak Regency with the aim of increasing community understanding and involvement in the process of drafting Village Regulations. Village Regulations are an important instrument for democratic, transparent, and accountable village governance. The activity implementation method was carried out through socialization, training, and direct mentoring for village officials, the Village Consultative Body (BAPEKAM), and community representatives. The results of the activity showed an increase in community knowledge regarding the function and urgency of village regulations, as well as a growing awareness to actively participate in public deliberation and consultation forums. However, ongoing efforts are still needed to strengthen community capacity, expand socialization, and ensure the involvement of all elements of society in a more inclusive manner. This service activity is expected to be the first step in encouraging more optimal community participation in participatory regulation-based village development.